Targeted treatment in a case series of AR+, HRAS/PIK3CA co-mutated salivary duct carcinoma - Rieke, Damian T.; Schröder, Sebastian; Schafhausen, Philippe; Blanc, Eric; Zuljan, Erika; von der Emde, Benjamin; Beule, Dieter; Keller, Ulrich; Keilholz, Ulrich; Klinghammer, Konrad (Frontiers in Oncology, 2023)
Background and Purpose: A subgroup of salivary duct carcinoma (SDC) harbor overexpression of the androgen receptor (AR), and co-occurring mutations in the HRAS- and PIK3CA-genes. The impact of genomic complexity on targeted treatment strategies in advanced cancer is unknown. Materials and Methods: We analyzed molecular and clinical data from an institutional molecular tumor board (MTB) to identify AR+, HRAS/PIK3CA co-mutated SDC. Follow-up was performed within the MTB registrational study or retrospective chart review after approval by the local ethics committee. Response was assessed by the investigator. A systematic literature search was performed in MEDLINE to identify additional clinically annotated cases. Results: 4 patients with AR+ HRAS/PIK3CA co-mutated SDC and clinical follow-up data were identified from the MTB. An additional 9 patients with clinical follow-up were identified from the literature. In addition to AR overexpression and HRAS and PIK3CA-alterations, PD-L1 expression and Tumor Mutational Burden > 10 Mutations per Megabase were identified as additional potentially targetable alterations. Among evaluable patients, androgen deprivation therapy (ADT) was initiated in 7 patients (1 Partial Response (PR), 2 Stable Disease (SD), 3 Progressive Disease (PD), 2 not evaluable), tipifarnib was initiated in 6 patients (1 PR, 4 SD, 1 PD). One patient each was treated with immune checkpoint inhibition (Mixed Response) and combination therapies of tipifarnib and ADT (SD) and alpelisib and ADT (PR). Conclusion: Available data further support comprehensive molecular profiling of SDC. Combination therapies, PI3K-inhibitors and immune therapy warrant further investigation, ideally in clinical trials. Future research should consider this rare subgroup of SDC.